(3QOY GdabQ Yf OYhi GdhdGjI GdcHQis - (3YHO GdhgGH Hf CMeO Hf Ydj GdnMnfaj, fSHg Edi eMeO GHf GdMfajI, GdTYQGfj, CHh eMeO , J (B973 (3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO abO OYGfi OGYi GdTabg Ydi WGFaI ef GdabQGA ai gPG GdReGf SehG CfaSge HGdUhajI hGOYhG GdhdGjI GdcHQi hge CVd ef GdCfYGe s
(3BNQgG (B:s
(3hCSCdg GdahR Ci GdXaQ HGdNjQ jhe GdeBH Ci GdQLhY Edi Gddg JYGdi hgh jhe GdbjGeI hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs